2020
DOI: 10.1186/s12906-020-02910-x
|View full text |Cite
|
Sign up to set email alerts
|

Belief in and use of traditional Chinese medicine in Shanghai older adults: a cross-sectional study

Abstract: Background: Traditional medicine is broadly used across Asian societies for various medical conditions and health concerns. However, there remains a wide disparity between users and non-use, which makes it imperative to understand the factors affecting the lay perception and utilization of traditional medicine. This study systematically examined the demographic, medical, and socioeconomic factors affecting belief in and use of traditional medicine among older adults of Shanghai, China. Methods: We used the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
5
27
0
1
Order By: Relevance
“…Our results suggest the percentage of CAM use in combination with CM was high among the older (≥60) age group patients. This result is consistent with the other studies in South-East Asian countries like India, Malaysia, and China [ 19 , 22 , 25 ]. One possible explanation is that younger people seek alternative and low-cost remedies for mild issues, while elderly patients seek traditional medical aid for severe complications.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results suggest the percentage of CAM use in combination with CM was high among the older (≥60) age group patients. This result is consistent with the other studies in South-East Asian countries like India, Malaysia, and China [ 19 , 22 , 25 ]. One possible explanation is that younger people seek alternative and low-cost remedies for mild issues, while elderly patients seek traditional medical aid for severe complications.…”
Section: Discussionsupporting
confidence: 93%
“…These findings could point to a trend among CAM users for high-income people to seek every available alternative for their health care benefit and well-being. However, a recent study found that, in addition to the four income levels, both the lowest and highest socioeconomic groups in China demonstrated an increased preference for CAM [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on TCM was more likely to attract attention from older adults, especially older women with chronic diseases. A cross-sectional study focused on older adults in Shanghai indicated that females were more likely to trust and use TCM [ 53 ]. Another study showed that having chronic lung disease was significantly associated with higher TCM practitioner utilization [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be because of the tendency of people with high incomes to seek out alternatives for their health care treatments and well-being. Although a recent study reported that along with the income distribution both the lowest and highest socioeconomic groups showed a strong preference for CAM in China (24).…”
Section: Discussionmentioning
confidence: 96%